Protective relay principles - Sleva, Anthony F. (CRC Press, 2009)
Focuses on probable power system failure modes and the important characteristics of the protective relays used to detect these postulated failures. This book covers important design considerations for working with overcurrent, over- and undervoltage, impedance, distance, and differential type relay functions, either individually or in combination.